Pelvic ultrasonography in premenarcheal girls: relation to puberty and sex hormone concentrations. Issue 2 (February 1985) - Salardi, S; Orsini, L F; Cacciari, E; Bovicelli, L; Tassoni, P; Reggiani, A
Abstract : Real time ultrasonography of the pelvic organs was performed on 114 normal premenarcheal girls aged between 2 years and 13 years 11 months. Values were obtained for total uterine length, anteroposterior diameters of the corpus and cervix, corpus/cervix ratio, and uterine and ovarian volumes and the resultant data were grouped according to age. It was concluded that there is no change in uterine size until approximately 7 years of age. Then the uterus begins to enlarge, both in prepubertal girls, in whom this is an age related function, and in pubertal girls, whose uterine growth is influenced not only by age but also by size and, independently of these two factors, by oestradiol concentrations. The onset of a modification in uterine morphology with a greater enlargement of the corpus than the cervix is also seen at age 7 years. Ovarian maturation begins in the very first years of life and, even in pubertal girls, seems to be influenced by age only and not by hormonal stimuli.